Respiratory Admissions Linked to Air Pollution in a Medium Sized City of the UK: A Case-crossover Study - Catherine A. Fitton; Bianca Cox; Munro Stewart; James Chalmers; Jill J. F. Belch (Aerosol and Air Quality Research)
Abstract This study, from the Tayside Pollution Research Programme (TPRP), aims to investigate the effects of air pollution on respiratory hospital admissions in adults and children < 16 y of age, over a 14-year period, in Dundee, Scotland (population circa 148,270). We conducted a case-crossover study using routinely collected healthcare records from Ninewells Hospital, Dundee, Scotland from 2004 to 2017. Respiratory hospitalisation events were linked to daily nitric oxide gases (NOx, NO2, NO) extracted from publicly available data over this period. We used distributed lag models to allow for delayed effects of air pollutants up to 14 days. A total of 34,192 hospital admissions for a respiratory condition were included in this study (children = 9,501; adults = 24,691). Respiratory admissions in children were significantly associated with cumulative 14-day exposure to NOx (RR for a 10 µg m−3 increase in concentration 1.020; 95% confidence interval 1.010–1.031), NO2 (RR 1.086; 95% CI 1.036–1.139) and NO (RR 1.033; 95% CI 1.016–1.052). Similar estimates were observed for acute respiratory infection categories in children. Effects appeared to be somewhat delayed, with the largest estimates mostly observed around lag 6. No significant association was seen for respiratory admissions in adults. This study shows that both NO and NO2 are associated with increased respiratory hospital admissions in children < 16 y of age, and that much more should be done to improve and enforce the established legal NOx pollution limits in cities for the sake of our children’s health.